Effect of friction stir processing on AZ91 Mg-alloy : a review - Rathod, Samir; Sharma, Daulat Kumar; Dani, Minal; Rank, Paras; Savaliya, Nikunj (Penerbit Universiti Kebangsaan Malaysia, 2021)
Generally properties of as-cast AZ91 soft Mg-alloy can be improved by conventional artificial aging. Conventional methods are time consuming and expensive process. Friction stir processing (FSP) based on working principle of Friction stir welding can replace the conventional processes at some extent. FSP generates enough heat in process to decrease grain size of coarse grains significantly and accordingly alter the properties. FSP extensive used for modification of morphology, grain refinement etc. and especially for as cast alloys. By performing FSP successfully on AZ91 alloy many properties of as-cast AZ91 can be changed significantly by varying friction stir process parameters. The improved resultant properties of Friction stir processed AZ91 alloys are credited to plastic deformation of alloy sheet by rotating non-consumable tool. Due to plastic deformation number of dislocation increase and it may by pile up, as a result the movement of dislocations are restricted and it required more stress to deform, thus strengthen the alloy. Tool in FSP plays crucial role, as tool shoulder and tool pin generate frictional heat, tool pin also used to improve material flow characteristics. FSP reduced grain size and enhanced various properties. This paper mainly reviews the effect of FSP on AZ91 Mg-alloy in terms of various properties enhancement.